2020
DOI: 10.1016/j.jclepro.2019.119105
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of consumer engagement in restaurant food waste mitigation in Poland: An exploratory study

Abstract: The growing magnitude of restaurant food waste undermines the environmental sustainability of the global sector of food service provision. The challenge of restaurant food waste is of particular concern for transitional and developing economies where food consumption out of home is becoming increasingly popular. In these markets, a large share of restaurant food waste comes from customer plates, which highlights changes to consumer behaviour as an important mitigation opportunity. Little is however known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 112 publications
3
91
1
1
Order By: Relevance
“…Filimonau et al (2019) note that without consumer awareness of both environmental and social impacts of food waste, it is difficult to promote food waste reduction. Conveying information about these impacts is important in raising consumers' awareness and motivation to reduce food waste [34]. Laven (2017) found that awareness of the impact of food waste on the environment supported positive behaviour change and hypothesised that restaurant managers are likely to see changes in food waste behaviour if they raise customer awareness of these impacts [30].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Filimonau et al (2019) note that without consumer awareness of both environmental and social impacts of food waste, it is difficult to promote food waste reduction. Conveying information about these impacts is important in raising consumers' awareness and motivation to reduce food waste [34]. Laven (2017) found that awareness of the impact of food waste on the environment supported positive behaviour change and hypothesised that restaurant managers are likely to see changes in food waste behaviour if they raise customer awareness of these impacts [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended that future food waste reduction initiatives tap into consumers' financial, social and environmental values. Awareness of food waste as an issue is an important precursor to motivating out-of-home food waste reduction [5,27,30,34,35]. Positively positioned messages are more likely to generate positive consumer responses and translate into behaviours to reduce food waste [27].…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations